2003
DOI: 10.1159/000073442
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of Atrial Natriuretic Peptides in Hemodialysis Patients

Abstract: Background: It is well known that plasma atrial natriuretic peptide (ANP) is an indicator of extracellular fluid volume expansion and that plasma ANP is considered to be a marker for setting the proper dry weight of HD patients. Although the plasma ANP is a prognostic predictor of cardiac death, the prognostic role of ANP in HD patients has yet to be elucidated. In this study, we investigated the prognostic role of ANP in HD patients. Methods: Plasma ANP concentrations were measured in 105 HD patients after HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Our findings complement and extend previously reported cohort studies of end-stage renal disease for the biomarkers ANP [8][12] and ADM [13] (Table 5). Most of these studies were done in small cohorts and/or short observation periods and only one study considered ADM. Our cohort differs from these earlier studies since we investigated baseline levels in patients before first dialysis treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings complement and extend previously reported cohort studies of end-stage renal disease for the biomarkers ANP [8][12] and ADM [13] (Table 5). Most of these studies were done in small cohorts and/or short observation periods and only one study considered ADM. Our cohort differs from these earlier studies since we investigated baseline levels in patients before first dialysis treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Both hormones are elevated in the early stages of CKD [4], [5] and were shown to be highly predictive for progression of CKD in nondiabetic patients [6], [7]. Elevated levels of ANP [8][12] and ADM [13] have been reported to be associated with cardiac events, overall and cardiovascular mortality in patients already on dialysis. Increased levels of ANP and ADM have been associated with higher mortality rates in cohorts of cardiac patients as well as in patients with type 2 diabetes mellitus [14][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, plasma natriuretic peptide concentrations are affected by the volume status [18], which varies particularly between the hemodialysis sessions. Still, plasma natriuretic peptide concentrations have proven to be a strong predictor of mortality in ESRD patients [4,19].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that plasma ANP level is an indicator of extracellular fl uid volume expansion and that plasma ANP is considered to be a marker for setting the adequate DW of HD patients [20] . Osajima et al [21] reported that the ideal post-HD ANP level is approximately 50-60 pg/ ml in patients without cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%